Unilateral Dorsal Root Ganglion Stimulation Lead Placement With Resolution of Bilateral Lower Extremity Symptoms in Diabetic Peripheral Neuropathy - Chapman, Kenneth B (Cureus, 2020)
Dorsal root ganglion stimulation (DRG-S) is a form of neuromodulation that can target specific dermatomes to obtain better coverage of the distal extremity. Previously proposed mechanisms of action for DRG-S focused on the dorsal root ganglion (DRG) itself, without consideration of orthodromic effects in the dorsal horn and antidromic effects on the nerve root and sympathetic chain. Diabetic peripheral neuropathy (DPN) is an axonal neuropathy that affects around half of all patients with diabetes mellitus, causing severe pain and sensory impairment in the distal extremities. We present a case of a patient with DPN in both feet, in addition to low back pain, who underwent a DRG-S trial with right T12 and S1 leads. The trial was performed unilaterally for seven days, allowing the patient to compare the treated versus the untreated (left) side. Pain, disability, general health status, and quality of life measures improved significantly. In addition to the significant pain relief in the low back and feet, the patient had near resolution of other DPN-related symptoms, including numbness, bluish discoloration, and allodynia of both feet. He also demonstrated functional and psychological benefits with only a single-sided lead. Overall, the placement of unilateral T12 and S1 DRG-S leads resulted in symmetric improvement of DPN symptoms. A possible mechanism of action is antidromic propagation of action potential signaling into the sympathetic chain to a central ganglion and then to the contralateral sympathetic chain. Given the DRG's ability to directly affect afferent sympathetic fibers with low-frequency stimulation, DRG-S may be an effective neuromodulatory treatment for DPN.